A contrastive study of the English and Myanmar configurations of process, participants, and circumstances from the systemic functional perspective - Win, Lai Yee (Universitas Ahmad Dahlan, 2024)
This study seeks to explore the similarities and distinctions inherent in the transitivity configurations of English and Myanmar from the Systemic Functional perspective. The investigation reveals that both languages share a commonality in comprising three fundamental elements: process, participant roles, and circumstantial elements. However, their degree of integration between processes and participants is comparatively limited. Salient distinguishing features emerge in terms of the sequencing of transitivity elements, their ellipsis, and salience. In English transitivity configurations, processes typically manifest after the first or second participant role, or both. In instances involving an empty Subject (It/There), the process immediately ensues. Additionally, the positional relations between processes and participant roles are more numerous. Circumstantial elements conventionally find placement at the clause's outset, between the first participant role and process, between the process and second participant role, or at the clause's conclusion. Ellipsis of participant roles may occur sporadically. Conversely, Myanmar transitivity configurations exhibit participant roles at the clause's beginning, with processes commonly positioned at the clause's culmination. The positional relations between processes and participant roles are less frequent. Circumstantial elements are conventionally situated at the clause's outset, between participant roles, or preceding the process. While ellipsis of processes is infrequent, ellipsis of participant roles transpires more frequently. These findings significantly contribute to the ongoing comparative analysis of transitivity configurations across languages, especially in the context of Myanmar and other global languages.